Social Responsibility Perguruan Tinggi Islam dalam Masyarakat Heterogen di Kota Palopo - Zainuddin S (Institut Agama Islam Negeri Palopo, 2016)
Social Responsibility Islamic college in a heterogeneous society is very important where there are various permaslahan ranging from social, religious, cultural, ethnic, and so on. Implementation of social responsibility programs implemented by IAIN college Palopo in the form of community service programs through research and community empowerment as a portion of Tridharma college. Various problems and constraints faced by IAIN Palopo is the lack of cooperation with the government, the lack of coordination of the implementation of activities, disseminate the results of research which is still low, the lack of real information regarding the condition of society, the implementation of the work program based on individual initiative, work programs aimed at specific groups, and there has been no work program, appropriate and sustainable for society.